GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2018)
A dataset containing 238602 species occurrences available in GBIF matching the query: TaxonKey: Picea abies (L.) H.Karst. HasGeospatialIssue: FALSE HasCoordinate: TRUE. The dataset includes 238602 records from 505 constituent datasets: 18 records from Vascular Plant Records up to 2010. 14 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 4 records from 2003-2004 Wokingham WHS Surveys. 30 records from Tercer Inventario Forestal Nacional. Ministerio de Agricultura, Alimentación y Medio Ambiente (España/Spain). 2396 records from Atlas des plantes vasculaires de Lorraine. 1 records from Some Plant Specimens from PE Herbarium in China from 1900 to 1950. 765 records from Flora of the Stołowe Mts.. 32 records from BRERC species records within last 15 years. 3574 records from Institute of Dendrology PAS, Flora of Sudety Mountains. 315 records from Welsh BSBI data (ex-VPDB dataset) at hectad resolution. 2 records from Konsekvensutredning naturmangfold E6 Åsen - Mære. 1 records from Vascular plant specimens of Toyama Science Museum. 44288 records from Finnish Floristic Database (Finnish Museum of Natural History Collections). 1005 records from Exotic plant occurrences in Wallonia. 984 records from Vascular plant field notes, NTNU University Museum. 29 records from National Trust for Scotland Species Records. 5 records from Artskartlegging flomsikringstiltak, Kvam 2013. 1 records from The Wildlife Information Centre - BioBlitz Events. 38 records from Living Collection of the Gothenburg Botanical Garden. 2 records from WTSWW Data: All Taxa (West Wales). 290 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 9182 records from Flora von Deutschland (Phanerogamen). 38 records from Environmental Monitoring Database Species data 1987 to 2015. 58 records from Local Wildlife Site Surveys Oxfordshire. 143 records from Vascular Plant Herbarium, Oslo (O). 1 records from Questagame weekly feed. 1 records from North Merseyside Local Species Data (DEFRA Grant 23169). 4 records from BoBO - Botanic Garden and Botanical Museum Berlin-Dahlem Observations. 42 records from BioFresh Pond Data. 79 records from A grid-based database on vascular plant distribution in the Meshchera National Park, Vladimir Oblast, Russia. 7 records from Allan Herbarium (CHR). 109 records from Floristic Databases of Mecklenburg-Pomerania - Higher Plants. 81 records from Gothenburg Herbarium - General (GBIF:IH:GB:Herbarium). 6 records from Vascular plant specimens of Nagano Environmental Conservation Research Institute, Nagano Prefecture. 3 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire. 1 records from Inventaire National du Patrimoine Naturel : Flore du Massif Armoricain. 2 records from Green Plant Herbarium (TRT). 23 records from Ecofact. 1911 records from Vegetation data from protected areas in Denmark (§ 3 in the Danish Nature Protection Act). 13 records from Distribution of Higher Plants in Greater Manchester. 12 records from Sistema de Información de la vegetación Ibérica y Macaronésica. 29 records from The New York Botanical Garden Herbarium (NY). 4685 records from Vascular Plants, Field notes, Oslo (O). 57 records from Vascular plant herbarium, NTNU University Museum. 16 records from Vascular plant herbarium, Tromsø Museum. 14 records from Kartlegging av dragehode. 4 records from Welsh Invertebrate Database (WID). 10 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 3694 records from Finnish Floristic Database (Literature Sources). 3 records from Ektomykorrhizen auf VIP Hainich (Wald). 16 records from Floristic records in the Moscow and Novgorod regions. 26 records from Estonian Nature Observations Database. 451 records from Vascular plant diversity in forests. 7 records from University of British Columbia Botanical Garden Collections (UBCBG). 154 records from Flora of Worcestershire. 1 records from KU Tunnel Kåfjord 2012 - Vegetasjon. 28 records from Merseyside BioBank (verified). 1 records from Records for Fife Nature Records Centre (Additional). 6 records from Data from Defra Family Organisations supplied to Staffordshire Ecological Record. 28 records from TWIC Biodiversity Field Trip Data (1995-2014). 1 records from Michigan State University Herbarium Vascular Plants. 1 records from Inventaire National du Patrimoine Naturel : Espèces Végétales Menacées de France métropolitaine. 112 records from ARKO kulturmarkseng. 3 records from SER Species-based Surveys. 132 records from Carnet en Ligne. 14 records from Spredning av fremmede arter med planteimport til Norge. 1209 records from Hatikka Observation Database. 29 records from Fauna and flora inventories (terrestrial and limnetic) from the South of Belgium. 24 records from SBT-Living. 319 records from LERN Records. 41 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1 records from Tag der Artenvielfalt im Taubental. 2 records from Botany Division, Yale Peabody Museum. 2032 records from Collections and observation data National Museum of Natural History Luxembourg. 1 records from Vom Gipfel ins Moor, Transekt im NSG Allgäuer Hochalpen. 1 records from Artenvielfalt am Schlern. 3 records from Vascular Plant Specimen database of Kanagawa Prefectural Museum of Natural History. 2 records from EDIT - ATBI in Gemer area (Slovakia). 1 records from EDIT - ATBI in Mercantour/Alpi Marittime (France/Italy). 1 records from R. L. McGregor Herbarium Vascular Plants Collection. 1 records from Kohlstattbrunnental. 1 records from Waldwandel in Monschau-Mützenich-Boverei. 1 records from Waldstück am Schullandheim Bad Bederkesa. 1 records from Leben in und an der Ruwer sowie ihren Nebenbächen. 1 records from Tag der Artenvielfalt mit SchülerInnen des Europa-Gymnasiums in Wörth am Rhein. 1 records from Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert sowie Umland. 1 records from Tage der Artenvielfalt rund um die Naturschutzstation Molsberg. 1 records from Freiburger Netzwerk Artenvielfalt. 1 records from Schwanheimer Wald. 1 records from Naturpark Drömling. 1 records from Perchtoldsdorfer Heide. 9 records from NRW Regional Data: North Wales. 1 records from Field Museum of Natural History (Botany) Seed Plant Collection. 535 records from Forest vegetation of the northeastern part of the Kostroma region (European Russia). 8 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 29 records from Moscow University Herbarium (MW). 576 records from Scottish SNH-funded BSBI records. 1262 records from Atlas Flora Danica. 4 records from Feriendorf des Kreises Groß-Gerau/Ober-Seemen. 1 records from Artenvielfalt auf dem Schulgelände. 1 records from VSN-Wiese. 1 records from Schulgelände Städtisches Gymnasium. 1 records from Mißmahlsche Anlage. 2 records from Walldorf-Wiesloch: "Natur über den Gleisen". 2 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 1 records from Himmelmoor. 1 records from Freiheitsring (Frechen). 1 records from Wupperaue bei Kemna (Wuppertal). 1 records from Lebensraum Stadt und Park. 1 records from Steinbruch Pluwig. 1 records from Halberg bei Neumorschen. 1 records from Prophetensee Quickborn. 1 records from Unterbrucker Weiher. 1 records from renaturierter Main (Kemmern bei Bamberg). 1 records from NABU-Projekt (Osterode am Harz) Südharzer Gipskarst. 1 records from Werremündung im Schwarzatal. 1 records from Schulhof und Anlagensee in Nellingen. 1 records from Feriendorf des Kreises Groß-Gerau Ober-Seemen/Gedern. 1 records from Schulgelände Dientzenhofer-Gymnasium (Bamberg). 1 records from Lindau im Bodensee. 1 records from Stadtpark Sulzbach-Rosenberg. 1 records from Lüner Holz (Lüneburg). 1 records from Bergkamen- Bergehalde Großes Holz. 1 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 1 records from Wiese am Waldrand (Gurtweil). 1 records from Streuobstwiese Kugelberg (Ulm). 1 records from Faberpark (Nürnberg/Stein). 1 records from Quarrendorfer Landschaftsschutzgebiet. 1 records from Wiese und Bach am Kleinen Eutiner See (Eutin). 1 records from Schulgelände Schule auf der Aue, Münster. 1 records from Gemeindegebiet Weikendorf (Marchfeld). 1 records from NABU Naturschutzhof Netttetal (Sassenfeld) e.V.. 1 records from Außenfeuerstelle Königsbol (Hartheim/Meßstetten). 1 records from Regionalpark(Hattersheim). 1 records from Industriegebiet (Kempen). 1 records from Wald am Schloss Wittgenstein Bad Laasphe. 1 records from Knechtweide (Kohlfurth). 1 records from 20 Jahre Naturschutzgebiet Dreienberg. 1 records from Gurgltal (Tarrenz). 1 records from Trockenrasen und Buchenwald in der Umgebung der Jugendherberge Bad Blankenburg. 1 records from Artenfülle um das Schalkenmehrener Maar. 1 records from Pilstingermoos. 1 records from Sudeniederung (Amt Neuhaus), Landkreis Lüneburg. 1 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 1 records from Promberg1. 1 records from katzenbuckel. 1 records from nazza. 1 records from Artenvielfalt auf der Weide - GEO-Hauptveranstaltung in Crawinkel. 1 records from Umgebung von Schorndorf. 1 records from Cuxhavener Küstenheiden. 1 records from Blumenrather Heide / Virneburg. 1 records from Wiese und Weide am Waldrand von Gusterath. 1 records from Artenvielfalt auf Restbauernhof. 1 records from Sonnentaugemeinschaft. 1 records from Rund um den Eichwald,Schulhof Friedrich Fröbel Gymnasium- Bad Blankenburg. 1 records from Langes Tannen. 1 records from Umgebung der Gesamtschule Hamburg-Winterhude. 1 records from Neckartalsüdhang (Horb). 1 records from NSG Hülenbuch Hörnle (Tieringen/Meßstetten). 1 records from NSG Karwendel. 2 records from Silbertor + Wasserbachtal (Rutesheim / Renningen). 1 records from Wald und Wiese am Buchwald. 1 records from Erlengraben/Lipp-Tal (Östringen). 1 records from Stausee (Oberdigisheim/Meßstetten). 1 records from Gelände des IVL (Zeckern). 2 records from Langes Tannen (Uetersen). 1 records from Erzental (Oberotterbach). 1 records from Freiburger Tag der Artenvielfalt. 1 records from Frauenholz (Holzmaden). 1 records from Königstetten. 1 records from Artenbestimmung. 1 records from Schule Sulzbach (Oberegg). 1 records from Schulgelände IGS Kaufungen. 1 records from GEO Hauptveranstaltung Tirol (Innsbruck). 1 records from Schlern - (Bozen). 1 records from Langenberger Forst am Ochsenweg/ Niebüll-Leck. 1 records from Naturschutzgebiet Bausenberg. 1 records from Naturschutzstation Schmidsfelden. 1 records from Angelberger Forst - Klassen 3 a und 3 b. 1 records from Gewann Krampf (Heilbronn). 1 records from Gemeinde Sursee. 1 records from Schlichemquelle (Tieringen/Meßstetten). 1 records from Waldränder der Frankenhöhe (Rothenburg ob der Tauber). 1 records from Schulgelände (Wetter). 1 records from Hamberger Brücke / Würmtal (Pforzheim). 1 records from GEO-Hauptveranstaltung (NLP Harz / Hochharz). 1 records from Trockenhang Greinhartsberg Edelfingen. 1 records from FFH-Gebiet Ahrbachtal. 1 records from AKG-Gelände (Bensheim). 1 records from Naturschutzgebiet Sistig-Krekeler-Heide. 1 records from Frau Voss. 8 records from IBF Monitoring of Lichens. 1348 records from IBF Monitoring of Vascular Plants. 6 records from The Fungal Collection at the Botanische Staatssammlung München. 1 records from Tiroler Landesmuseum Ferdinandeum. 324 records from A grid-based database on vascular plant distribution in Vladimir Oblast, Russia. 4 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 1 records from Sukzession Industriebrache. 1 records from Ober-Olmer Wald 09. 1 records from Neißetal. 1 records from Grünes Germersheim. 1 records from Flora und Fauna im Brexbachtal. 59 records from Dorset Sites of Nature Conservation Interest (SNCI) species records 2000-2008. 1 records from Fliegenhaupt Marksuhl. 1 records from Cuxhaven Schlosspark, Klasse 5e- Amandus-Abendroth-Gymnasium. 1 records from Vascular plant specimens of Akita Prefectural Museum. 130 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 1533 records from Effects of vegetation clearing on vascular plants in power line clearings southeast Norway. 26194 records from INPN - Données flore des CBN agrégées par la FCBN. 5131 records from Dutch Vegetation Database (LVD). 2 records from River Blackwater historic river corridor surveys. 9596 records from Norwegian Species Observation Service. 2 records from vegetation releves on grassland gridplots in 2007. 1060 records from Geographically tagged INSDC sequences. 9234 records from VegetWeb - Repositorium von Vegetationsaufnahmen. 20 records from Ickworth Estate species data held by The National Trust. 79 records from Natural Resources Wales Regional Data : Mid-Wales. 2 records from vegetation releves on grassland gridplots 2007-2009. 401 records from Lund Botanical Museum (LD). 5 records from ArtenFinder. 21 records from Rotherham Biological Records Centre - Non-sensitive Records from all taxonomic groups. 12 records from National System of Protected Areas in Poland - Plants. 4 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Verified data. 3 records from Flora d'Andorra. 2 records from Heritage Trees of Ireland. 317 records from Phenological observations of biota on the territory of Prioksko-Terrasnyi biosphere reserve. 36 records from Faun. 2 records from Sutton Hoo species data held by The National Trust. 65 records from FloraCAT: Banco de datos de los cormófitos de Cataluña. 8297 records from The DNA and Sample Repository at AIT. 2875 records from National Wetland Inventory (NV). 1 records from Vascular Herbarium, NMBU. 14 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 1 records from Anglesey Abbey wildlife species data held by The National Trust.. 22 records from TransForest vegetation data. 2 records from National Plant Monitoring Scheme - England, Scotland, Wales. 7 records from Herbarium Senckenbergianum (FR). 97 records from Gloucestershire Historic Wildlife Sightings prior to 1st Jan 2000. 47 records from KTU Pinophyta. 6 records from MfN - Fossil plants (Cenophytic). 1 records from Feuerlöschteich, Wald und Dünen in den Holmer Sandbergen. 1 records from Naturschutzgebiet Lüneburger Heide. 1 records from BB-Biodiversität a. 1 records from Oberes Schindelbachtal. 1 records from Raus in die Natur. 1 records from Listhof und Umgebung. 1 records from Biotope entdecken im Kockmecker Siepen (Sauerland). 1 records from Naturpark Sternberger Seenland. 1 records from Schieferbrüche. 1 records from Schiller Gymnasium Hof 10b. 2 records from "Wildnis erleben" - "Vielfalt erlebbar machen" - Botanischer Garten u.Chrimmitschauer Wald. 1 records from Bayerische Donau - Blindheim Donaubrücke. 1 records from Rund um die Sausenburg. 1 records from BB-Biodiversität b. 1 records from Mönchspark. 1 records from Werl macht sich auf die Suche. 1 records from Dornwanger Moos. 1 records from Schanzenanlage Bergham. 2 records from Artenvielfalt am "Grünen Band" bei Coburg: 20 Jahre Wiedervereinigung. 1 records from 6. Tag der Artenvielfalt Hockenheim Thema: Wald 12.-14.6.2009. 1 records from Bayerische Donau - Leipheim. 1 records from LBV 100 - Artenvielfalt am Rothsee. 1 records from Mangfalltal. 1 records from Artenerfassung für Jedermann in der Grundschule Kirchboitzen. 1 records from Schriesheimer Steinbruch. 1 records from Baggerseen bei Krauchenwies. 1 records from Schulgelände des Schulzentrums am Himmelsbarg. 1 records from Sahrbachtal Kreis Ahrweiler. 2 records from GEO-Hauptveranstaltung in "Wildtierland". 1 records from Eschlberg Thalhausen. 1 records from Kühmark bei Wetzlar. 1 records from Biosphärenpark Wienerwald - Pfaffstätten. 1 records from Sandloch - Höhle. 1 records from Freiburger GEO-Tag der Artenvielfalt. 1 records from English Nature Oxford City Surveys. 1 records from Hatfield Forest species data held by The National Trust.. 2 records from RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 3194 records from naturgucker. 148 records from SEWBReC Vascular Plants (South East Wales). 56 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 1 records from Yorkshire Wildlife Trust - Non-sensitive records from all taxonomic groups. 1 records from City of Edinburgh Natural Heritage Service - Natural Heritage Service Data. 17931 records from Occurrence Data of Vascular Plants collected or compiled for the Flora of Bavaria. 2 records from "Schwarzwassertal" bei Pobershau. 1 records from Höhle am Neuweg / Sächsische Schweiz. 1 records from GEO-Tag der Artenvielfalt der Klasse 7c am Gymnasium Allee im Wohlers Park. 1 records from Aktion der Klasse H2 in Simmelsberg. 1 records from Pflanzen und Tiere im Burgwald. 1 records from Wälder im Hainbachtal. 1 records from Bodenteicher Seewiesen. 1 records from Langes Tannen(LMS), Klasse 5d. 1 records from Gronau - auf der Suche nach dem Neunauge. 1 records from Tongrube bei Hettstedt. 1 records from Wiesen am Treffpunkt Freizeit. 1 records from Tag der Artenvielfalt in Heidelberg. 1 records from Weinberg Reichersdorf. 1 records from Bernhardsthal. 1 records from Schulwald Grundschule Brügge. 1 records from LK 11 im Mönchspark. 2 records from Schulzentrum "Parc Hosingen". 1 records from Biosphärenpark Wienerwald - Wiener Steinhofgründe. 1 records from Kaniswall/ Gosener Wiesen an der Spree. 1 records from Pöhlberg bei Annaberg. 1 records from Natur-Erlebnisgebiet der Naturschutz-Akademie Hessen und Umgebung. 1 records from Fürstenberger Ralley Teil 3. 1 records from Waldfläche im Natur-Erlebnis-Pfad Pfinztal. 1 records from Bannwald Burghauser Forst. 1 records from GEO-Hauptveranstaltung im Nationalpark Bayerischer Wald. 1 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 1 records from Landschaftsschutzgebiet Schmutterwald. 1 records from Schulgelände Paul-Gerhardt-Schule. 2 records from FFH-Gebiet "Calwer Heckengäu". 1 records from Tiere und Pflanzen am Pfannenbach. 1 records from Innenhöfe der Gesamtschule Berger Feld/ Gelsenkirchen. 1 records from Schulinnenhöfe (Gelsenkirchen). 1 records from Landschaftsschutzgebiet Buchhorst 4. 1 records from Kleinstbiotop mit Schulteich/Weißwasser. 24 records from IBF Monitoring of Plant Galls. 1 records from Sudeniederung (Amt Neuhaus). 1 records from Zwickau- Schwanenteich. 1 records from Draubiotop Lavamünd. 1 records from Mühlenbach bei Buxtehude. 1 records from Hoher Stein Kallenhardt. 1 records from Klütwald. 1 records from Schulhof A.-Lindgren-Schule (Elmshorn). 1 records from Biosphäre Bliesgau. 1 records from Gelände des Schulzentrums am Himmelsbarg. 1 records from Waldstück Bremerhagen LK Bio Kl. 12. 1 records from Dalbekschlucht. 1 records from Birkenloh. 1 records from WildesMoor bei Schwabstedt. 1 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 1 records from Hainbachtal bei Oelsnitz / V.. 1 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 1 records from Naturparadies in Gräfenhausen am Trifels (bei Annweiler). 1 records from Schulhof der Astrid-Lindgren-Schule Elmshorn. 1 records from Heilpflanzen im Hainbachtal. 1 records from Brander Wald (Stolberg). 1 records from GymnQuerfurt. 1 records from Spielwiese. 1 records from Ludwigshofen. 1 records from Westerwälder Umwelt- und Naturschutztag Limesgemeinde Hillscheid. 1 records from privater Garten. 2 records from Geschützter Landschaftsbestandteil - GLB "Troppach". 961 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 1 records from Naturhausgarten. 1 records from Umgebung der Grundschule Oderberg. 1 records from Wangerooge. 1 records from Hainbachtal in Oelsnitz/V.. 1 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 1 records from Ortelsbruch - Hangmoor bei Morbach. 1 records from Triebesbach (Zeulenroda-Triebes). 1 records from Bodenseeufer Radolfzell. 1 records from Flusswerder in der Weser (Hameln). 1 records from Verwilderter Hausgarten mit angrenzendem Gelände (Laufenburg-Hochsal). 1 records from Zielbach (Töll). 1 records from Regenrückhaltebecken (Zeulenroda). 1 records from Überall ist Wunderland. 1 records from LaBoOb02. 459 records from FloVegSI - Floristical and fitocenological database of ZRC SAZU. 2 records from Vascular Plants, Observations, Oslo (O). 6 records from Commissioned surveys and staff surveys and reports for Scottish Wildlife Trust reserves - Verified data. 22 records from Biodiversitätsdatenbank des Landes Salzburg. 109 records from SER Site-based Surveys. 3 records from Plant specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 11 records from EURISCO, The European Genetic Resources Search Catalogue. 4 records from inatura - Erlebnis Naturschau Dornbirn. 4 records from Nordic Genetic Resources. 11 records from Water Colours of Fungi by Konrad Schieferdecker at the Botanische Staatssammlung München. 8 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 117 records from Biologiezentrum Linz. 2018 records from Observations du Conservatoire botanique national du Bassin parisien.. 5 records from Herbarium Berolinense. 1 records from Herbarium (UNA). 22 records from Botany registration database by Danish botanists. 3 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 4 records from Paleobiology Database. 18 records from New Zealand Virtual Herbarium. 16 records from Herbarium of Jyväskylä University Museum. 9 records from Auckland Museum Botany Collection. 1 records from Institut Botanic de Barcelona (IBB-CSIC-ICUB), BC-Plantae. 3 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Gobierno de Extremadura. 1 records from Herbarium of Vascular Plants Collection of the University of Extremadura (Spain). 2 records from Herbario ABH (Universidad de Alicante). 1 records from Universitat de Girona: HGI-Cormophyta. 3 records from Aranzadi Zientzi Elkartea. 4 records from Jardín Botánico de Córdoba: Herbarium COA. 1 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO. 4 records from CSIC-Real Jardín Botánico-Colección de Plantas Vasculares (MA). 57 records from The Fungal Collection of Helga Große-Brauckmann at the Botanische Staatssammlung München. 3 records from NMNH Extant Specimen Records. 1 records from East Ayrshire Species Database. 2 records from Ibaraki Nature Museum, Vascular Plants collection. 17 records from Ireland's BioBlitz. 1 records from Inventario nacional de especies vegetales y animales de uso artesanal. 384 records from Waarnemingen.be - Non-native plant occurrences in Flanders and the Brussels Capital Region, Belgium. 1 records from Catálogo Florístico Histórico de Navarra. Gobierno de Navarra. 3 records from Natural History Museum (London) Collection Specimens. 105 records from BRERC species records recorded over 15 years ago. 6 records from Tropicos Specimen Data. 1038 records from The Fungal and Lichen Collections at the Herbarium Marburgense. 10 records from The Exsiccatal Series "Triebel, Microfungi exsiccati". 17 records from The Lichen Collection at the Botanische Staatssammlung München. 83 records from IBF Monitoring of Fungi. 1 records from Artenvielfalt Kreis Gießen. 1 records from Föhrenried (Fronreute und Baindt). 1 records from Döchtbühlwald (Bad Waldsee). 1 records from Truppenübungsplatz Panzerkaserne Böblingen. 1 records from Lassentiner Moor (Niepars). 1 records from Naturgrundstück (Eutin). 1 records from Fuchsloch (Mohlsdorf/Ostthüringen). 1 records from Kinder- und Jugendferiendorf des Kreises Groß-Gerau - Gedern/Ober-Seemen. 2 records from "Schlechteberg" Ebersbach/Sa.. 1 records from Dierloch, nördlicher Mooswald (Freiburg-Hochdorf). 1 records from Feriendorf des Kreises Gedern (Ober-Seemen). 1 records from Waldsee. 1 records from Isarufer. 1 records from Lech 2001. 1 records from Ehmkendorf. 1 records from LauWi. 1 records from Kloster Eberbach. 1 records from Feriendorf Ober-Seemen. 1 records from Küstenschutzwald. 1 records from Siegen/ Gymnasium Am Löhrtor. 1 records from Im Bauerngarten. 3 records from Herbarium of the Department of Natural Forests (Forest Research Institute) - Plants. 1 records from Rekartlegging av skog i Kvam i 2015 og 2016. 9 records from All taxa records for Leicestershire and Rutland between 1987 and 2016. 45 records from A common plants survey of vascular plants in South Northumberland and Durham, United Kingdom. 42 records from Finnish Floristic Database (Small Collections). 49 records from National Trust Species Records. 53 records from NINA botanical collection. 1 records from Merseyside BioBank Active Naturalists (unverified). 2368 records from Other BSBI Scottish data up to 2012. 36 records from CONN. 499 records from iNaturalist Research-grade Observations. 20 records from NRW Regional Data: all taxa (excluding sensitive species), West Wales. 192 records from Hertfordshire Flora Survey Records 1987-2005. 3 records from DBG Kathryn Kalmbach Herbarium. 2 records from Vascular Plant Herbarium, UiB. 10 records from Australia's Virtual Herbarium. 1 records from BRFC Black Rock Forest Consortium Herbarium. 55 records from Norwegian Biodiversity Information Centre - Other datasets. 2 records from Tallinn Botanic Garden. 1045 records from Données ONF Faune-Flore-Fonge. 1 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 63 records from Oskarshamn herbarium (OHN). 559 records from Inventaire National du Patrimoine Naturel : Flore du Limousin. 5 records from Plant specimens of Otaru City Museum. 3 records from River Pant historic river corridor surveys. 83 records from Miscellaneous records held on the Cofnod database. 189 records from Stabbetorp - Floristiske registreringer 2016. 1 records from Desert Botanical Garden Herbarium. 15 records from BBOWT Local Wildlife Sites Surveys 1994-2003. 157 records from The importance of host tree age, size and growth rate as determinants of epiphytic lichen diversity in boreal spruce forest.. 2 records from Flora of Słowiński National Park, Poland. 2 records from Plant Specimen Database of Tama Forest Science Garden, Forestry and Forest Products Research Institute, Japan. 45895 records from Artportalen (Swedish Species Observation System). 1 records from KU E16 Slæn - Tvinno. 5 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 1 records from Victorian Biodiversity Atlas. 6 records from Kartlegging av spredning av fremmede bartrær. 18 records from Vascular plant herbarium, Agder naturmuseum og botaniske hage. 5 records from Herbier Louis-Marie (QFA) - Collection de plantes vasculaires. 1 records from City of Edinburgh Natural Heritage Service - Historical Records. 750 records from BioFokus. 1742 records from Spatially explicit database of tree related microhabitats (TreMs). Version 1.2. Integrate+ project. 13 records from Phase 2 Woodland Survey of Wales. 6 records from Isle of Man historical wildlife records 1995 to 1999. 1 records from Finchingfield Brook historic river corridor surveys. 1 records from Species within North Ayrshire from 1984 - Present. 39 records from Local Wildlife Site Surveys Berkshire. 24 records from Isle of Man historical wildlife records 1990 to 1994. 1 records from Digitization of plant specimens from Rhoen and Vogelsberg (FLAD). 156 records from RECORD Vascular Plant Data. 486 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 208 records from Shropshire Ecological Data Network database. 3 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 377 records from Karplanter i vernet barskog og edelløvskog. 6074 records from Vascular plants in Denmark recorded under the The Nationwide Monitoring and Assessment Programme for the Aquatic and Terrestrial Environments (NOVANA). 332 records from FLORIVON. 6 records from Local BioBlitz Challenge 2013. 100 records from Species plots from the Norwegian Vegetation Mapping Programme. 2 records from Lothian Wildlife Information Centre Secret Garden Survey. 1 records from Spredning av fremmede arter med tømmerimport til Norge. 2 records from LNHG Biological Records Dataset. 10 records from SANT Herbarium vascular plants collection. 1 records from UTEP Plants (Arctos). 46 records from PlutoF platform observations. 2 records from Naturalis Biodiversity Center (NL) - Botany. 8 records from Bryophytes, fungi and lichens on dead wood. 2 records from Spermatophyte collection of Himeji City Science Museum. 1 records from Fremmede arter - Planteimport, Engebråten Planteskole. 79 records from Dorset Sites of Nature Conservation Interest (SNCI) species records pre 2000. 15 records from Online Atlas of Vascular Plants 2012-2020. 797 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 4 records from Dorset SSSI Species Records 1952 - 2004 (Natural England). 10 records from Isle of Man wildlife records from 01/01/2000 to 13/02/2017. 5 records from University of Vienna, Institute for Botany - Herbarium WU. 556 records from Jordal. 2 records from Phanerogamic Botanical Collections (S). 1 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 1 records from OEH Atlas of NSW Wildlife. 3 records from Ektomykorrhizen auf VIP Alb (Wald). 13 records from NBIS Records to December 2016. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences